Вплив теплопровідності покриття на зміну градієнта температури в інструменті з ПКНБ - Манохін, Андрій Сергійович; Клименко, Сергій Анатолійович (Національний технічний університет "Харківський політехнічний інститут", 2020)
Виконаний модельний аналіз впливу теплопровідності захисного покриття TiAlN на градієнт температури в інструменті, оснащеному надтвердим композитом ПКНБ, при обробці загартованої сталі. Встановлено, що захисне покриття має суттєвий вплив на градієнт температури в різальному інструменті з надтвердого композиту ПКНБ в тому випадку, коли коефіцієнт теплопровідності покриття не перевищує 15 Вт/мК. Такі покриття обумовлюють зниження температури на поверхні розділу системи «основа з ПКНБ-покриття» при точінні загартованої сталі на 100–300 °С. Збільшення теплопровідності покриття зніжує його теплозахисний ефект по відношенню до матеріалу основи різального інструменту.

A model analysis of the effect of thermal conductivity of the TiAlN protective coating on the temperature gradient in a tool equipped with a super-rigid kiborite composite was performed in the processing of hardened steel. The finite element method solved a two-dimensional linear non-stationary problem of thermal conductivity with boundary conditions of the 3rd kind. At the control points on the support part of the tool as the limit conditions to take the temperatures determined when turning hardened steel with a cutting speed of 1.3 m/s. Given the presence of a gradient of material velocities, the chip model is divided into layers with different speeds. The amount of shrinkage of the chips is taken 2, which corresponds to the chip speed vc = 0.65 m/s. The movement of the chips along the contact surface of the tool was simulated taking into account the mass transfer in the region where the elements were specified. It is shown that increasing the cutting speed leads to a decrease in the temperature gradient in the tool, which is associated with a decrease in the friction coefficient, as well as the cutting force. The magnitude of the temperature drop in the coating depends on its thermal conductivity and the maximum temperature on the contact surface of the tool. It was found that the protective coating has a significant effect on the temperature gradient in the cutting tool of the superhard PcBN composite in the case when its coefficient of thermal conductivity of the coating does not exceed 15 W/mK. Such coatings cause a decrease in the surface temperature of the section of the system «basis of PcBN coating» when turning hardened steel at 100–300 °C. If the coefficient of thermal conductivity of the coating is higher than 15 W/mK, it has a minimal effect on the temperature on the surface of the section of the system «basis of PcBN coating», despite the fact that the value of thermal conductivity of the composite PcBN much more.
The influence of cooling conductivity on the change of temperature gradient in the PCBN tool
Keywords: захисне покриття; теплозахисний ефект; різальний інструмент; protective coating; thermo protective effect; cutting tool